A high fat diet alters metabolic and bioenergetic function in the brain: A magnetic resonance spectroscopy study. (July 2016) - Raider, Kayla; Ma, Delin; Harris, Janna L.; Fuentes, Isabella; Rogers, Robert S.; Wheatley, Joshua L.; Geiger, Paige C.; Yeh, Hung-Wen; Choi, In-Young; Brooks, William M.; Stanford, John A.
Abstract: Diet-induced obesity and associated metabolic effects can lead to neurological dysfunction and increase the risk of developing Alzheimer's disease (AD) and Parkinson's disease (PD). Despite these risks, the effects of a high-fat diet on the central nervous system are not well understood. To better understand the mechanisms underlying the effects of high fat consumption on brain regions affected by AD and PD, we used proton magnetic resonance spectroscopy ( 1 H-MRS) to measure neurochemicals in the hippocampus and striatum of rats fed a high fat diet vs. normal low fat chow. We detected lower concentrations of total creatine (tCr) and a lower glutamate-to-glutamine ratio in the hippocampus of high fat rats. Additional effects observed in the hippocampus of high fat rats included higher N-acetylaspartylglutamic acid (NAAG), and lower myo-inositol (mIns) and serine (Ser) concentrations. Post-mortem tissue analyses revealed lower phosphorylated AMP-activated protein kinase (pAMPK) in the striatum but not in the hippocampus of high fat rats. Hippocampal pAMPK levels correlated significantly with tCr, aspartate (Asp), phosphoethanolamine (PE), and taurine (Tau), indicating beneficial effects of AMPK activation on brain metabolic and energetic function, membrane turnover, and edema. A negative correlation between pAMPK and glucose (Glc) indicates a detrimental effect of brain Glc on cellular energy response. Overall, these changes indicate alterations in neurotransmission and in metabolic and bioenergetic function in the hippocampus and in the striatum of rats fed a high fat diet. Highlights: Measures indicating glutamate turnover were increased in the hippocampus but not the striatum of high fat rats as measured by 1 H-MRS. Serine concentrations were decreased in the hippocampus of high fat rats as measured by 1H-MRS. Total creatine was decreased in the hippocampus of high fat rats as measured by 1 H-MRS. pAMPK protein content was decreased in the striatum of high fat rats as measured by Western blot. pAMPK was positively correlated with measures indicating improved neural function and negatively correlated with glucose.